2020
DOI: 10.1007/s12144-020-01087-3
|View full text |Cite
|
Sign up to set email alerts
|

If school walls could talk: A mixed-method study of physical space marking in promoting multiculturalism

Abstract: Combining two qualitative and a quantitative method, we explored whether school’s physical environment promotes multicultural values or reflects intergroup climate in two multiethnic communities in Croatia. Croatia offers unique context for this study because minority youth from two ethnic groups use their right on minority language education and hence attend separate minority schools. Results show that the representation of ethnic symbols in schools is a reflection of inter-ethnic relations in the specific in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Its recognition process mainly includes stroke data acquisition, data preprocessing, line element classification (from coarse classification to fine classification), and finally the regularization of line elements, that is, fitting. The first is the digital description of strokes [ 17 ]. The collected stroke trajectories are stored in the designed data structure according to certain rules.…”
Section: Methodsmentioning
confidence: 99%
“…Its recognition process mainly includes stroke data acquisition, data preprocessing, line element classification (from coarse classification to fine classification), and finally the regularization of line elements, that is, fitting. The first is the digital description of strokes [ 17 ]. The collected stroke trajectories are stored in the designed data structure according to certain rules.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, growing up in communities that primarily expose children to one side of the divide and a particular ethos-such as display of flags or murals-may have an impact on children's developing foundations of their identities (Connolly et al 2009). For instance, work in similar contexts like Croatia showed that in more conflict-affected schools tend to over-represent group symbols that emphasize differences, whereas in more harmonious intergroup settings higher emphasis was put on the shared identities and symbols (Jelić et al 2022). For Kosovo's segregated context we found that the preference for the presented ethnic symbols is more pronounced for the Serb (minority) children, who show stronger preferences for ethnic symbols than Kosovar Albanian (majority) do.…”
Section: Discussionmentioning
confidence: 99%